Building a custom high-throughput platform at the Joint Genome Institute for DNA construct design and assembly—present and future challenges. Issue 1 (5th November 2020) - Blaby, Ian K; Cheng, Jan-Fang
Abstract: The rapid design and assembly of synthetic DNA constructs have become a crucial component of biological engineering projects via iterative design–build–test–learn cycles. In this perspective, we provide an overview of the workflows used to generate the thousands of constructs and libraries produced each year at the U.S. Department of Energy Joint Genome Institute. Particular attention is paid to describing pipelines, tools used, types of scientific projects enabled by the platform and challenges faced in further scaling output.